Enfermedades parasitarias más comunes en caninos - Becerra Segura, Cristian Marcelo (2020)
A parasite is an organism that uses another living being as a food source. There are a wide variety of parasites that can affect canines, in this article we will talk about the most common, such as detecting them, the problems they can cause. We can classify parasites into canines into two groups: Internal parasites: These are those that live inside the canine. They can stay in your digestive tract, in your blood, in your internal organs, etc. Some are visible, such as worms, but others are microscopic in size External parasites: They are insects or arachnids that live or feed on the skin of the canine. They eat blood or skin cells and usually cause itching and discomfort.